2015
DOI: 10.1002/ange.201503983
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting an Epoxide Hydrolase Virulence Factor from Pseudomonas aeruginosa Protects CFTR

Abstract: Opportunistic pathogens exploit diverse strategies to sabotage host defenses.P seudomonas aeruginosa secretes the CFTR inhibitory factor Cif and thus triggers loss of CFTR, an ion channel required for airway mucociliary defense.However, the mechanism of action of Cif has remained unclear.I t catalyzese poxide hydrolysis,b ut there is no knownr ole for natural epoxides in CFTR regulation. It was demonstrated that the hydrolase activity of Cif is strictly required for its effects on CFTR. As mall-molecule inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…An immunoassay selective for the diol product confirmed conversion of 14,15-EET to 14,15-DHET by Cif, but not by the structurally conserved mutant Cif-D129S (Fig. S1B), which is enzymatically inactive (16).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…An immunoassay selective for the diol product confirmed conversion of 14,15-EET to 14,15-DHET by Cif, but not by the structurally conserved mutant Cif-D129S (Fig. S1B), which is enzymatically inactive (16).…”
Section: Resultsmentioning
confidence: 98%
“…In particular, the administration of a LXA 4 analog in mice challenged intratracheally with P. aeruginosa led to reduced neutrophil infiltration, weight loss, and bacterial burden, resulting in overall lessening of disease severity (15). An alternative strategy may be to inhibit Cif activity with a targeted small-molecule approach (16,37). In addition to blocking the enzymatic degradation of lipid mediators, inhibitors would also block the ability of Cif to subvert rescue of CFTR by recently approved clinical correctors (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cif has been shown to decrease the concentration of the Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) on the apical surface of lung epithelial cells, sabotage the inflammation resolution signaling between the epithelial cells and the immune system, and hinder mucociliary clearance of bacteria [3,4,5]. The crystal structure of Cif showed that it utilizes a His-Tyr pair instead of the canonical Tyr-Tyr pair for epoxide ring orientation and hydrolysis intermediate stabilization [6]. aCif from Acinetobacter nosocomialis was subsequently shown to belong to this new class of Cif-like (Cfl) epoxide hydrolases [7].…”
Section: Introductionmentioning
confidence: 99%
“…One of them triggers degradation of the cystic fibrosis transmembrane conductance regulator (CFTR). 9 The CFTR inhibitory factor (Cif), which has putative orthologs in several opportunistic airway pathogens, 10 is an epoxide hydrolase. Its catalytic activity affects host mucociliary and antiviral defenses and appears to facilitate infection of the lungs.…”
Section: Introductionmentioning
confidence: 99%